Rancang Bangun Aplikasi Pemesanan Dan Penjualan Berbasis E – Commerce Pada Produk UMKM Desa Kiringan Kabupaten Magetan (Studi Kasus: Ds. Kiringan Kec. Takeran Kab. Magetan) - Pratama Tegar Al Hafizh (LPPM Universitas Merdeka Madiun, 2022)
The advancement of information technology is currently growing rapidly,especially the development of the internet has become a necessity to findinformation. The use of the internet allows everyone to easily carry out the processof buying and selling online known as